One modification of the promax method for confirmative taxonomical analysis - Momirović Konstantin (Psihologija, 2004)
Paper presents one simple method for fuzzy or hard confirmative classification of some set of variables on the basis of hypothetical fuzzy or hard classification from that set which also enables an estimation of the similarities of taxons, collected by the same method. This procedure is defined by transformation of reparametrized matrix of object projections on principal components. The transformation is achieved by matrix of unconstrained Promax solution transformed in Mahalanobis form. The efficiency of computer program for that method was demonstrated with one numerical example.